T-STUB COMPONENT BEHAVIOR OF THE BEAM TO COLUMN BOLTED FLANGE CONNECTION BASED ON A NUMERICAL ANALYSIS AND EN 1993-1-8 DESIGN CODES - Solodovnyk, Y.; Riumin, V. (Municipal economy of cities. Series: «Economy science», 2023)
Nodal joints uniting separate elements of steel structures are the most important parts of the whole structure. For the tensile zone of a connection, the study of its stress-strain state up to the limit of exhaustion of its bearing capacity is of greatest interest. There exist different design approaches to obtain the ultimate capacity of a tension-zone of a steel joint, both numerical and analytical methods. In the presented paper this has been realized using a general-purpose finite element analysis package. The application of numerical methods for modelling the tensile performance of the T-component makes it possible to compensate for the lack of data on full-scale experimental studies. Despite the widespread use of finite element analysis packages, there are still no clear guidelines for creating numerical models of such connections. Numerical analysis has taken into account important effects such as the nonlinear behavior of the material and the contact interaction of its individual elements. Finite element analyses should represent the reality in an accurate way while not being too time consuming to be set up and run. That means appropriate parameters and phenomena, such as element types or loading procedure, should be compiled in a way suitable to the problem at hand, so that the discrepancy between reality and model is sufficiently small. A FE-model with wrong representation of reality can be solved correctly with FEA, but will thereby provide inaccurate results. Therefore, one needs understanding about FE parameters and their influence on time to execute the procedure effectively. When these conditions are met, the possibility to analyze larger number of T-stubs with less user modification opens up. The analytical method for the calculation of the properties of a bolted joint established by the structural Eurocodes proposes the T-stub as a component for the characterization of the tension and compression zones in moment joints. Using the component method, which is the basis for the calculation of joints according to the EN 1993-1-8 design codes, the value of the ultimate tensile force for the T-shaped component of the dimensions adopted in the work was obtained; the obtained values of the ultimate forces were further used in the numerical experiment.